Cellular distribution of estrogen receptors alpha in the rabbit ovary during pregnancy and lactation - Mahmoud Abd-Elkareem; Sulaiman Mohammed Alnasser; Alotaibi Meshal; Mohsen A. Khormi; Mohammed A. Alfattah (Scientific Reports)
Abstract Pregnancy and lactation is a critical period for rabbit production. Estrogen (E2) and estrogen receptors alpha (ERA) are essential during pregnancy and lactation and their importance stems from their role in ovarian activities. Despite extensive research into the roles of E2 and its receptors in the ovary, cellular distribution of ERA in the rabbit ovary during pregnancy, after parturition and during lactation remained unexpectedly elusive. To achieve this aim, eighteen healthy sexually mature New Zealand white rabbit does (2.97 ± 0.2 kg) were raised in the animal house, faculty of medicine, Assiut University. The females rabbit were mated by fertile bucks; the day of mating as was considered Day 0 of pregnancy. Ovaries were collected at 12 h, 3, 7, 14 days post-mating, at parturition and at 10 days of lactation and fixed then processed for immunohistochemistry of ERA. In the present study, the cellular distribution of ERA in the rabbit ovary during pregnancy, postpartum and during lactation revealed moderate ERA immunolocalization in the ovarian surface epithelial cells, stroma cells, fibroblast cells of the tunica albuginea, and follicular cells of the primordial and primary follicles. The growing and small antral follicles showed strong cytoplasmic and nuclear ERA immunolocalization in the granulosa cells and theca folliculi cells. The large antral (graafian) and pre-ovulatory follicles showed moderate to strong ERA immunolocalization in the granulosa cells, corona radiata cells, cumulus oopherous cells, oocyte, theca interna cells and theca externa cells. The atretic antral follicle showed strong cytoplasmic and negative nuclear ERA immunolocalization in the apoptotic granulosa cells and strong cytoplasmic and nuclear ERA immunolocalization in the proliferated theca interna cells. The endothelial cells of the ovarian blood vessels, the interstitial gland cells and telocytes showed strong cytoplasmic and nuclear ERA immunolocalization. The corpus luteum (CL) during pregnancy till parturition showed moderate to strong ERA immunolocalization in the large lutein cells, small lutein cells and luteal endothelial cells. The regressed CL in the rabbit ovary 10 days of lactation showed weak ERA immunolocalization in the regressed large lutein cells and moderate cytoplasmic and negative nuclear ERA immunolocalization in the small lutein cells. Interestingly, the rabbit ovary during lactation showed abundant interstitial gland with strong ERA immunolocalization in the interstitial gland cells. This work highlights the role of ERA in the ovulation, folliculogenesis, lutenization and luteal regression in the rabbit during pregnancy and lactation which contribute to enhancing this animal’s reproductive success.